KEAMANAN JARINGAN MENGGUNAKAN UNIFIED THREAT MANAGEMENT PADA SERVER BERBASISKAN LINUX - Heru, Bambang; Benny, Benny; Defendy, Defendy; Hento, Wahyu (Bina Nusantara University, 2007)
UTM is an application which integrated many security features become a single hardware platform. The reasonbehind this research is to build a system that protects the network in St. Bellarminus school. Research method that hasbeen used in this research is spiral method, whereas the development of the application is continues and can be modifiedeasily if there is new version of the security tools implemented in the application, or if there is a better security tools to beused. The outcome of the system is very good, because it can protects the network: cross-platform firewall, IntrusionDetection System, Proxy Server, email protection against virus and spam. In conclusion, the application can producehigh effectiveness with low cost and this application is very useful in monitoring and configuring the network in St.Bellarminus school.Keywords: security network, unified threat management, anti virus, server, proxy, firewall